Effect of increasing pump speed during exercise on peak oxygen uptake in heart failure patients supported with a continuous‐flow left ventricular assist device. A double‐blind randomized study. (8th January 2014) - Jung, Mette Holme; Hansen, Peter Bo; Sander, Kaare; Olsen, Peter Skov; Rossing, Kasper; Boesgaard, Soeren; Russell, Stuart D.; Gustafsson, Finn
Abstract : Aims: Continuous‐flow left ventricular assist device (CF‐LVAD) implantation is associated with improved quality of life, but the effect on exercise capacity is less well documented. It is uncertain whether a fixed CF‐LVAD pump speed, which allows for sufficient circulatory support at rest, remains adequate during exercise. The aim of this study was to evaluate the effects of fixed versus incremental pump speed on peak oxygen uptake (peak VO2 ) during a maximal exercise test. Methods and results: In CF‐LVAD (HeartMate II) patients exercise testing measuring peak oxygen uptake (VO2 ) was performed on an ergometer bike twice in one day: once with fixed pump speed (test fix ) and once with incremental pump speed (test inc ). The order of test fix and test inc in each patient was determined by randomization. During test inc pump speed was increased from the baseline value by 400 rpm/2 min. Fourteen patients (aged 23–69 years) were included with a mean support duration of 465 ± 483 days. Baseline CF‐LVAD speed was 9357 ± 238 rpm and during test inc speed was increased by a mean of 1486 ± 775 rpm. Mean peak VO2 was significantly higher in test inc compared with test fix (15.4 ± 5.9 mL/kg/min vs. 14.1 ± 6.3 mL/kg/min; P  = 0.012), corresponding to a 9.2% increase. All exercise tests (n = 28) were adequately performed with RER > 1. Conclusion: Increasing pump speed during exercise augments peak VO2 in patients supported with CF‐LVADs. An automatic speed‐change function in future generations of CF‐LVADs might improve functional capacity.